2023
DOI: 10.1002/edn3.412
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a nutria (Myocastor coypus) environmental DNA assay highlights considerations for sampling methodology

Abstract: Nutria (Myocastor coypus) is a semiaquatic rodent species that is invasive across multiple regions within the United States. Here, we evaluated a qPCR assay previously described for use in Japan for application across invasive populations in the United States. We also compared two environmental DNA sampling methodologies for this assay: field filtration of large volumes of water passed through filters versus direct sampling of small volumes of water. We validated assay specificity, generality, and sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Similar to Mangan et al. (2023), this study confirmed that the assay was able to detect nutria in the field, and that filtering water in the manner practiced was effective for DNA capture. The findings revealed a link between water levels and nutria detection, with higher water levels generally associated with higher concentrations of eDNA.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to Mangan et al. (2023), this study confirmed that the assay was able to detect nutria in the field, and that filtering water in the manner practiced was effective for DNA capture. The findings revealed a link between water levels and nutria detection, with higher water levels generally associated with higher concentrations of eDNA.…”
Section: Discussionsupporting
confidence: 86%
“…Initially introduced from South America to the United States for fur farming during the late 1800s, nutria established wild populations throughout the country (Carter & Leonard, 2002). Notable hotspots of nutria invasion include areas near the Gulf of Mexico, the Pacific Northwest, and the mid‐Atlantic region of the USA (Mangan et al., 2023). Their foraging habits involve digging through soil in search of roots and rhizomes and result in the destruction of wetland vegetation (Jojola et al., 2005; LeBlanc, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation